ISLAM, PEREMPUAN DAN PENDIDIKAN - Mujiburrahman Mujiburrahman (Marwah: Jurnal Perempuan, Agama dan Jender, 2014)
The article will discuss various viewpoints on the issues affecting women in Islam, and how they influence the views regarding women education. Their views generally can be divided into conservative, progressive and philosophical. All these views, in general, regard that like men, women are obliged to search for knowledge. In Indonesia, since the 19th century, women have already been involved in learning religion. However, for some cultural reasons, in this period, the access for women to modern education was still limited. On the other hand, from the 20th century up to now, like male Muslims, Indonesian female Muslim have more opportunies in education. Moreover, the symbolic-philosophy of complementary relations between male and female can also become an alternative to conservative or liberal philosophy of education